B Lymphocyte memory in X-linked Lymphoproliferative disease (XLP) - Coraglia, Ana Carina (2010)
X-linked lymphoproliferative disease (XLP) is a severe immunodeficiency characterized by hypogammaglobulinemia, fulminant infectious mononucleosis, and/or lymphoma associated to mutations of the SH2D1A gene, encoding SAP (signaling lymphocytic activation molecule-associated protein). The initial encounter with Epstein Barr virus (EBV) triggers a massive response that leads to a fatal outcome in around 50% of the XLP individuals. Most surviving patients develop hypogammaglobulinemia and eventually B cell lymphoma. B lymphocyte development seems to be normal, but there is a marked reduction of memory B cells (CD27+ B lymphocytes). In addition, Th1 cell mediated immune responses predominate over Th2 responses. Hypogammaglobulinemia and failure to develop a long term humoral immune response can be explained because both the germinal center (GC) reaction and GC formation in secondary lymphoid organs are greatly impaired both in human XLP and in experimental SAP deficiency. Non switched memory B cells (IgM+, IgD+, CD27+ B lymphocytes) persist in XLP patients, suggesting that in spite of the lack of a GC reaction, some subgroups of memory B lymphocytes can play a role in immune homeostasis in these patients. In addition, their persistence in the presence of EBV infection, could perhaps be associated to late occurrence of extranodal B-cell lymphoma, which is another pathological condition associated to the absence of SAP in humans.